Baricitinib: therapeutic potential for moderate to severe atopic dermatitis. (2nd October 2020) - Calabrese, Laura; Malvaso, Dalma; Chiricozzi, Andrea; Tambone, Sara; D'Urso, Dario Francesco; Guerriero, Cristina; Peris, Ketty
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease mediated by multiple signals including janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. Current therapeutic armamentarium consists of a limited number of drugs which may result in the insufficient management of AD. Preclinical evidence regarding inhibition of JAK/STAT led to the development of a promising class of therapeutics, namely, JAK inhibitors. Baricitinib, a novel JAK1/JAK2 inhibitor is currently under investigation in AD clinical trials. Areas covered: This review offers an overview of Baricitinib and examines clinical efficacy and safety data in patients with moderate-to-severe AD. Expert opinion: Baricitinib showed promising preliminary data in terms of efficacy in phase II and III trials, with a very rapid onset of response and great improvements of itch and sleep disturbances. These aforementioned aspects combined with the advantage of an oral formulation have reduced drug production costs compared to biologic agents and could lead to consideration of baricitinib as a first line systemic treatment. Also, in some countries, it could be a therapeutic option in the case of contraindication or failure of conventional systemic drugs prior to biologic therapies. Data related to long-term safety and efficacy will be important to refine the place-in-therapy of this drug.